Evaluation of DNA vaccines developed against Mycoplasma struthionis sp. nov. str. Ms01 in ostriches - De Wet, Bertus (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.